MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN MENGGUNAKAN METODE JARIMATIKA PADA SISWA KELAS VI SDN GELAM 4 CIPOCOK JAYA - Zerri Rahman Hakim (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
This research based on the low ability arithmatic of multiplication of student 6th grade in SDN GELAM 4 CIPOCOK JAYA. This research supposed to increase the Arithmatic skill of multiplication using Jarimatika Method. The subject of this research is 6th grade of SDN GELAM 4 CIPOCOK JAYAwith 34 students. This research is CLASSROOM ACTION RESEARCH. Arithmatic skill is basic skill that each student should have it. This data get from observation and student’s interview. The learning process start from multiplication concept. Int the practice, the teacher acts as fasilitator. The teacher domenstartes Jarimatika Multiplication Formation. Andthen, the teacher give some question for student to teach arithmatic skill using Jarimatika Method as solution. In the end of learning process, each of students taking the evalution test. And the result shown if Jarimatika method can improve the ability of student 6th grade SDN GELAM 4 CIPOCOK JAYA in arithmatic multiplication. In the main topic , integers can be seen from the result of average score in siklus I get 68,7 and increasing until 92 on siklus II. Activities of students increasing until 41,7% in siklus I and get increasing until 75,2% in the end of siklus II. Keywords : Counting Skill in Multiplication. Jarimatika Method.